Aboveground biomass of understorey vegetation has a negligible or negative association with overstorey tree species diversity in natural forests. Issue 2 (21st October 2015) - Zhang, Yu; Chen, Han Y. H.; Taylor, Anthony R.
Abstract: Aim: The positive relationships between tree species diversity, aboveground biomass and productivity of overstorey tree layers have been widely reported in tropical, temperate and boreal forest ecosystems. However, no consensus has been arrived at on the association between overstorey tree species diversity and the functions of understorey vegetation, such as the biomass of understorey tree, shrub, herb and bryophyte layers, despite their critical contributions to the diversity and functions of natural forests. Location: Canadian forest (42°37′ to 68°14′ N; 53°25′ to 134°46′ W; 4 to 2170 m elevation). Methods: We employed Canada's National Forest Inventory dataset to evaluate the influences of overstorey tree species diversity on the aboveground biomass of each forest stratum by accounting for the effects of climate, site condition and stand age. Results: We found that aboveground biomass of overstorey trees and total aboveground biomass were positively associated with overstorey tree species richness; however, the aboveground biomass of understorey trees, shrubs, herbs and bryophytes were not associated or were negatively associated with overstorey tree species richness, evenness and life‐history trait variations. Main conclusions: Our results show positive associations between aboveground biomass of the overstorey tree layer and overstorey tree species diversity over a wide range of climate, local site conditions and stand ages in natural forests. However, contrary to previous findings that more tree species result in higher levels of multiple ecosystem functions, including understorey plant functions, our results demonstrate that the aboveground biomass of understorey vegetation has either a negligible or negative association with overstorey tree species diversity. The negative associations between overstorey tree species diversity and understorey biomass possibly resulted from greater resource filtering by overstorey trees in ecosystems with more diverse overstorey tree species.